Effect of particle size on flame retardancy and mechanical properties of hydroxyethyl diphosphate modified aluminum hydroxide intrinsic polyethylene terephthalate. Issue 21 (19th January 2021) - Shi, Jianping; Zeng, Wei; Yang, Zhiwang; Li, Ju; Zhao, Pufang; Li, Hongtao; Yan, Xingxing; Wen, Na; Lei, Ziqiang; Chen, Denglong; Guan, Jie
Abstract: Organic–inorganic hybrid flame retardant was obtained by modifying aluminum hydroxide with different particle size with 1‐hydroxyethylidene‐1, 1‐diphosphonic acid. The structure of the organic–inorganic hybrid flame retardant is characterized by Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscopy, while 1 H‐NMR spectroscopy only characterizes specific samples. The thermal stability and flame retardancy of the samples were analyzed by thermogravimetric analysis, limiting oxygen index (LOI), vertical combustion of UL‐94 and cone calorimeter. The results show that the modified 10 μm aluminum hydroxide has a better effect than the 25 μm aluminum hydroxide and 100 nm aluminum hydroxide. Compared with pure polyethylene terephthalate (PET), the LOI value of the best sample is increased by 24.4%, and UL‐94 V reaches V‐0 level. Heat release rate, total heat release rate, and carbon monoxide production rate decreased by 45.8%, 33.2%, and 41.5%, respectively, compared to pure PET. The results showed that the aluminum hydroxide with a particle size of 10 μm exhibited the best flame retardant effect, which could be attributed to the decomposition of organic phosphoric acid and the dehydration of aluminum hydroxide, yielding a higher amount of residual carbon. Abstract : Functional monomer HA, terephthalic acid and ethylene glycol are copolymerized by chemical reaction to prepare intrinsic flame‐retardant copolyesters (HAnPETs). After drying, the flame‐retardant copolyester particles are processed by an injection molding machine, and the molded flame‐retardant copolyester passes a series of flame‐retardant tests.